(untitled) (Academia Science Repository, 2023)
This article describes the role of fine art in human life and how it is inextricably linked with the science of color, which is considered a branch of fine art. He gives extensive reflections on ”color contrast“ and ”the concept of color" and briefly outlines a number of necessary methodological recommendations for artists related to color in the creative process.